GOVERNMENT SUPPORT TO ENCOURAGE THE USAGE OF ICT IN AGRICULTURE: PERSPECTIVE FROM GOVERNMENT OFFICERS IN THE NORTHERN REGION - Nur Amalina Ismail; Muhammad Aliuddin Bakar; Muhammad Amirruddin Ismail; Nur Aliah Sorfina, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The agricultural sector in Malaysia is a crucial contributor to the country's economy. However, Malaysia has had one of the lowest agricultural productivity growth rates in recent years, trailing Indonesia, the Philippines, Vietnam, and Thailand. The industry is dominated by smallholders with an ageing farmer population, low levels of mechanisation, and a high dependence on labour, resulting in numerous inefficiencies and low productivity. This study explores government efforts to boost agricultural ICT adoption. assesses the effectiveness government's initiative and the obstacles it faces in promoting ICT in this industry. An in-person interview was conducted to collect perspectives and insights from eleven government officials from grades 27 to 52. The data was analysed using manual thematic analysis. The findings indicate that the ICT initiatives encompass a range of technological solutions and financial support. The efficiency, frequency, exposure, and variety of facilities are key performance indicators for evaluating the success of government initiatives. However, age, knowledge, cost, expertise, and inadequate network accessibility hinder ICT integration in agriculture. To address these challenges, it is imperative that all relevant stakeholders, including both governmental and private entities, collaborate to enhance the various tiers of information and communication technology